How Supportive Psychotherapy being Implemented on Pediatric Cancer Patient Experiencing Depression Symptom? - Maghfiroh, Intan Putri; Alfian, Ilham Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
This article aims to describe supportive psychotherapy interventions on cases of depression in pediatric cancer patients using a qualitative case study approach. Participants in this study were a male child patient with a medical diagnosis of Osteosarcoma, aged 10 years 10 months, who were being treated in hospital. A series of examinations were carried out through interviews, observations and several psychological tests including graphic tests (DAP and BAUM) and CBCL to determine the psychological dynamics of participant so that appropriate interventions could be designed. The examination results showed that the participant had an innate temperament profile that led to internalizing behavior, especially withdrawal behavior. Coupled with the ability to regulate emotions that have not been optimally trained, this increases the risk of emotional aspects being disturbed in a sick condition. The supportive psychotherapy intervention carried out showed a reduction in depressive symptoms so that the participants began to be interested in returning to their usual enjoyable activities, such as playing games. The response to interactions with other people also returns so that they do not show withdrawal behavior. The participant also showed more frequency of smiling. Refusal and irritability when asked to eat begins to decrease.Artikel ini bertujuan untuk mendeskripsikan intervensi psikoterapi suportif untuk menangani kasus depresi pada pasien anak kanker dengan metode pendekatan kualitatif studi kasus. Partisipan dalam penelitian ini merupakan seorang pasien anak dengan diagnosis medis Osteosarcoma, berusia 10 tahun 10 bulan, berjenis kelamin laki-laki yang sedang dirawat di rumah sakit. Rangkaian pemeriksaan dilakukan melalui wawancara, observasi dan beberapa tes psikologi di antaranya tes grafis (DAP dan BAUM) dan CBCL untuk mengetahui gambaran dinamika psikologis partisipan sehingga dapat disusun intervensi yang sesuai. Hasil pemeriksaan menunjukkan bahwa partisipan memiliki profil temperamen bawaan yang mengarah ke perilaku internalizing terutama perilaku menarik diri. Ditambah dengan kemampuan regulasi emosi yang belum telatih optimal membuat menambah risiko terganggu aspek emosinya dalam kondisi yang sakit. Intervensi psikoterapi suportif yang dilakukan menunjukkan pengurangan gejala-gejala depresi sehingga partisipaan mulai berminat kembali melakukan aktivitas-aktivitas menyenangkan yang biasa dilakukan yaitu bermain gim. Respon interaksi dengan orang lain pun kembali sehingga tidak menarik diri. Partisipan juga menunjukkan frekuensi tersenyum lebih banyak. Penolakan dan iritabilitas saat dimminta untuk makan pun mulai berkurang.